2018
DOI: 10.3389/fpsyg.2018.00936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Processing of Food Images: A Conditional Role for Viewing in Preference Formation

Abstract: Previous research suggested a role of gaze in preference formation, not merely as an expression of preference, but also as a causal influence. According to the gaze cascade hypothesis, the longer subjects look at an item, the more likely they are to develop a preference for it. However, to date the connection between viewing and liking has been investigated predominately with self-paced viewing conditions in which the subjects were required to select certain items from simultaneously presented stimuli on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Interestingly, this notion of extra information integration under doubt is also compatible with other findings from our laboratory on the cognitive mechanisms underlying the evaluation of food images. Particularly, across two connected studies, Wolf et al (2018Wolf et al ( , 2019 found that subjects tended to gaze longer at images for which they felt uncertain about the evaluation, completely against the prevailing notion in the literature that "viewing leads to liking." Again, the finding of longer gazing at items that are not clearly liked or disliked can be interpreted in terms of volatility.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, this notion of extra information integration under doubt is also compatible with other findings from our laboratory on the cognitive mechanisms underlying the evaluation of food images. Particularly, across two connected studies, Wolf et al (2018Wolf et al ( , 2019 found that subjects tended to gaze longer at images for which they felt uncertain about the evaluation, completely against the prevailing notion in the literature that "viewing leads to liking." Again, the finding of longer gazing at items that are not clearly liked or disliked can be interpreted in terms of volatility.…”
Section: Discussionmentioning
confidence: 94%
“…963290-0403). Eye positions were recorded using Eye Tribe, an eye-tracking device at 60 Hz sampling rate (The Eye Tribe Aps, Denmark); a system with sufficient reliability for present purposes 22 , 54 , 55 .…”
Section: Methodsmentioning
confidence: 99%
“…We chose food images as a relevant category for evaluative processing with bivalent items 15 – 17 that elicit a complex integration of visual and non-visual features (e.g., flavor, caloric value, nutritive attributes) 18 21 . Previous research in our lab had further shown that the rating of individual food items provides a suitable opportunity to investigate the cognitive mechanisms underlying evaluation 22 . Here, we examine how explicit, supraliminal positive or negative predictions impact on the evaluation of appetitive or aversive food images.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation mirrors other findings in our own laboratory, undercutting the notion that viewing leads to liking. Using an absolute-evaluation paradigm with food images, we found that in most situations, viewing time was not associated with increased preference formation when subjects evaluated food images one at a time, rather than making choices between pairs of images (Wolf et al, 2018(Wolf et al, , 2019. The entire pattern of data suggested that increased viewing times occurred under indecision or deliberative processing, that is, when subjects engaged in a prolonged effort of information integration.…”
Section: Additive Versus Multiplicative Role Of Attention In Preferenmentioning
confidence: 88%
“…The monitor screen was set approximately 62 cm from the chin-rest. Subjects used a keyboard to give manual responses, and their eye movements were recorded by Eye Tribe, an eye-tracking device at 60 Hz sampling rate (The Eye Tribe Aps, Denmark); a system with sufficient reliability for present purposes (Ooms et al, 2015;Wolf et al, 2018;Zommara et al, 2018). To prevent the heat buildup of Eye Tribe, a small universal serial bus (USB) fan was used at the same time.…”
Section: Apparatusmentioning
confidence: 99%